CASE STUDY ON IFOSMADIDE-INDUCED CYSTITIS - PASULA, SRINIVAS; HUMAIRA HUSSAINI, SYEDA ZAINEB; GV, NAGARAJU (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Adverse drug response elaborates, is response to the drug which is caused to an organ or tissue damage for normal dose in the patients for the prophylaxis, 22 years male patient was hospitalized with complaints of relapsed Hodgkin’s lymphoma (HL) using post-Adriamycin, Bleomycin, Binblastine, and Dacarbazine regimen. The patient had treated HL with ICE regimen, after 24 hours of treatment with prescribed the ICE regimen, The patient was observed with following symptoms like vomiting, painful burning micturition and laboratory investigations reported. Abnormal then we suggested Mesna 3 days for prophylactic course then symptoms were not found and patient was discharged. We conducted Adverse drug reaction (ADR) assessment was resulted as probable type and we can probably prevent this type of ADR.